2016
DOI: 10.1371/journal.pone.0162029
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Long Term FTY720 Treatment on Endothelial versus Smooth Muscle Cell Signaling to S1P in Rat Mesenteric Arteries

Abstract: The sphingosine-1-phosphate (S1P) analog FTY720 exerts pleiotropic effects on the cardiovascular system and causes down-regulation of S1P receptors. Myogenic constriction is an important mechanism regulating resistance vessel function and is known to be modulated by S1P. Here we investigated myogenic constriction and vascular function of mesenteric arteries of rats chronically treated with FTY720. Wistar rats received FTY720 1mg/kg/daily for six weeks. At termination, blood pressure was recorded and small mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…FTY720 is an immunosuppressive agent and is widely used in the treatment of autoimmune diseases, such as multiple sclerosis, asthma and several kinds of cancers, such as renal cancer, liver cancer and hepatic cancer [26][27][28]. Although many studies have demonstrated its excellent antitumour effects, to our knowledge, there have been no reports about its effect in sacrum chordoma [29,30]. Fortunately, our study concluded that FTY720 is as effective in sacrum chordoma as it is in other tumours.…”
Section: Discussionmentioning
confidence: 57%
“…FTY720 is an immunosuppressive agent and is widely used in the treatment of autoimmune diseases, such as multiple sclerosis, asthma and several kinds of cancers, such as renal cancer, liver cancer and hepatic cancer [26][27][28]. Although many studies have demonstrated its excellent antitumour effects, to our knowledge, there have been no reports about its effect in sacrum chordoma [29,30]. Fortunately, our study concluded that FTY720 is as effective in sacrum chordoma as it is in other tumours.…”
Section: Discussionmentioning
confidence: 57%
“…Despite its high specificity and efficacy, clinical use of FTY720 for cancer therapy is restricted due to its capability of inducing profound bradycardia at an antineoplastic dose. FTY720 is rapidly phosphorylated and becomes an agonist for G protein-coupled sphingosine 1 phosphate receptors (S1PRs), activating a signaling cascade in atrial myocytes that reduces heart rate. , Furthermore, phosphorylated FTY720 is also known to induce immunosuppression by inhibiting lymphocyte egress from the thymus and secondary lymphoid organs, resulting in lymphopenia, a reduction of peripheral lymphocytes . FTY720 analogues designed to prevent phosphorylation through conformational restraint were shown to eliminate these adverse effects. ,, The analogues down-regulate nutrient transport proteins and demonstrate potent anticancer efficacy in leukemia and prostate cancer models while maintaining normal heart rate.…”
Section: Introductionmentioning
confidence: 99%